Efficiency and voluntary redistribution under inequality - Masaki Aoyagi; Naoko Nishimura; Yoshitaka Okano (Osaka University, Institute of Social and Economic Research (ISER), 2017)
This paper presents an experimental analysis of 2x2 coordination games in which player 1 earns a substantially higher payoff than player 2 except in the inefficient equilibrium where they earn the same payoffs. The main focus is on the comparison of two treatments with and without the ex post redistribution stage in which both players may voluntarily transfer their payoffs earned in the game to the other player. We find that (1) the transfer opportunity raises the probability of coordination on an efficient equilibrium, (2) a transfer from player 1 to player 2 is positive, and is higher when player 2 chooses the action corresponding to the efficient equilibrium, and hence (3) the transfer opportunity tends to improve the efficiency and equity of the final outcome. Furthermore, these tendencies are stronger when the two players have conflicting interests over the two equilibria than when they have common interests.
Keywords: C72; D03; D31; D63; 330; heterogeneity; equity; efficiency; transfer; reciprocity; laboratory experiments